Covert advertising as inadmissible presentation of information. Issue 1 (2014) - ,; ,; ,; ,
<x xml:space="preserve">Abstract</x> Purpose – The purpose of this paper is to identify and redefine the categories of covert advertising, to demonstrate the covert aspects of advertising in the press, to provide a high‐quality comparison of three leading Slovenian newspapers and to prepare a model for future researchers. Design/methodology/approach – In this article, the authors defined, analyzed, and explored covert advertising. In the first part, the authors used descriptive approach and method of compilation. In the empirical part, the authors used content analysis to research texts of covert advertising; the authors used analytical approach. Data were analyzed with the help of the computer programme SPSS. Findings – The results of the research indicate that covert advertising appears on a daily basis in daily newspapers and these articles are visually more attractive to garner greater attention from readers and offer numerous visual presentations. Research limitations/implications – The first limitation is presenting a lack of literature in this area, especially very poor knowledge of covert advertising in English, American and German literature. There is not a single word that around the world marked the same phenomenon. This research is limited to print media; it cannot be generalized to all media. This is a survey of ads where the authors cannot rule out subjective assessments. Originality/value – The significance of this research is that texts with covert advertising in Slovenia were for the first time scientifically investigated. The research approach and methodological instruments could be used as a model, a simplified representation of reality for future researches. <ack> <x xml:space="preserve">Acknowledgements</x> The authors thank the two anonymous reviewers for the constructive comments on this paper. </ack>